“Sharp Sybaritic” Retrofuturistic Deco Realism: Some Preliminary Notes on the 1980s Airbrush Art - Kassaveti, Ursula-Helen (Imaginations)

(untitled) (York University, 2019)
Originating in the late 19th century, the airbrush spray gun was widely used in the mid-20th century as a photo retouch tool in advertising, while it contributed to the introduction of Photorealism in the early 1970s. The “LA scene” of the same decade popularized airbrush art through masterful illustrations. Using a variety of different representations, the 1980s airbrush art became the distinctive postmodern popular style of the decade, especially through the publication and distribution of posters and postcards, as well as in advertising. Although the 1990s saw its decline, in the late 2000s the 1980s airbrush art seems to be resurgent thanks to the Internet, providing an escapist narrative for the post-2007-2008 financial crisis landscape.